PEDAGOGICAL-PSYCHOLOGICAL FEATURES OF DEVELOPMENT OF METHODOLOGICAL READINESS OF FUTURE TEACHERS (TAMADDUN NURI JURNALI, 2024)
Pedagogical-psychological features of development of methodological readiness of future teachers, aspects of pedagogical qualification and psychological preparation of teachers are covered in this article. It is also reported that these characteristics are important in preparing teachers for effective pedagogical activities and providing quality education to students.